Deep Characterization of SARS-CoV-2: An Overview - Ul Haq, Ehsan (Archives of Medical Laboratory Sciences, 2021)
The coronavirus epidemic has become one of the major health concerns all over the world recently. Like other strains of coronavirus, this strain also spreads through a droplet-based transmission that is the main cause of its worldwide spread. Several trials of antiviral medicines related to the control of the virus have already begun globally but still one of the main problems is the lack of a viable treatment option. An extensive amount of research is still taking place to organize the data associated with genomics and proteomics of its original strain SARS-CoV-2 alongside other mutant strains. This review summarizes the related up-to-date research that is going on the structural organization of the genome and proteome of the virus. *Corresponding Author: Ehsan Ul Haq; Email: ehsanulhaqsani5@gmail.com; BBTF17E116@uos.edu.pk Please cite this article as: Ul Haq E. Deep Characterization of SARS-CoV-2: An Overview. Arch Med Lab Sci. 2021;7:1-6 (e2). https://doi.org/10.22037/amls.v7.33616